A near-net-shape forming and thermal stress optimization process for complex component metal materials

CN122955901APending Publication Date: 2026-10-23HEBEI INST OF MACHINERY ELECTRICITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611296922.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种复杂构件金属材料近净成型与热应力优化工艺,解决了常规冷却介质传热速率固定导致构件不同截面冷却不同步、体积收缩不均匀引发热应力集中与变形开裂,以及单一热处理无法彻底释放残余应力的问题

Benefits of technology

[0045]1、本发明通过利用自适应相变传热流体结合随形温控流道建立动态热场控制机制,聚亚烷基二醇遇热脱溶析出并在流道内壁附着形成富聚合物绝热层,温度降低时重新溶解,配合去离子水相变汽化吸收潜热,自适应调节流体同模具界面的接触热阻,针对复杂构件不同截面厚度区域实施物理热阻调节,缩小模具整体温度梯度并维持各区域冷却速率趋向一致,抵消凝固时间差带来的体积收缩差异,抑制成型过程产生翘曲变形与微裂纹。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955901A_ABST
    Figure CN122955901A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal forming, and discloses a near-net forming and thermal stress optimization process for complex component metal materials, which comprises the following steps: adding an antioxidant 703 and benzotriazole into propylene glycol, heating and dissolving to prepare a composite additive solution, mixing polyalkylene glycol, the composite additive solution and deionized water to generate a self-adaptive phase change heat transfer fluid, combining with thermal stress simulation analysis to reversely design a conformal temperature control runner in a forming die, injecting molten aluminum alloy liquid into a preheated die to apply die casting pressure, synchronously pumping the heat transfer fluid into the conformal temperature control runner to control the cooling rate of a thermal stress concentration area to complete near-net forming, and after demolding, implementing multistage temperature rising and heat preservation heat treatment on the primary formed component and slowly cooling in the furnace. The application relies on the heat release of the fluid to generate an adiabatic layer and the water phase change heat absorption mechanism, adaptively adjusts the contact thermal resistance, synchronously maintains the cooling rate of each cross section thickness area, offsets solidification shrinkage internal stress and stabilizes the component size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal forming technology, specifically to a near-net-shape forming and thermal stress optimization process for complex component metal materials. Background Technology

[0002] Near-net-shape forming technology for metal materials relies on molds to directly form liquid metal into parts that are close to their final shape. During the forming stage, the solidification of the liquid metal needs to be controlled by a cooling circuit. With the upgrading of industrial manufacturing requirements, the formed components have geometric abrupt features such as variable cross-section junction areas, asymmetric protrusion areas, and thin walls. The heat contained in different cross-section thickness areas varies, resulting in inconsistent natural heat dissipation conditions at their respective locations.

[0003] Traditional molding cooling processes mainly involve introducing water or heat transfer oil into the mold flow channels for cooling. Conventional cooling media have a fixed heat transfer rate and maintain equal heat exchange capacity when flowing through various areas of the mold. They cannot adaptively adjust the thermal resistance to address the dynamic thermal field at the interface between thick and thin sections. The fixed cooling mode causes deviations in the cooling rate of the molten metal in different thickness areas, leading to asynchronous solid-state phase changes and volume shrinkage in various parts. The uneven physical shrinkage process continuously accumulates thermal stress inside the material, especially forming high-intensity stress concentrations at geometric change nodes.

[0004] When the accumulated internal stress exceeds the material's yield limit, it will directly cause the component to warp and deform or even crack macroscopically, damaging the dimensional accuracy of the molded part. In addition, the heat treatment process after molding mostly adopts a single heating and holding mechanism, lacking a step-by-step temperature control for the non-equilibrium structure in the die-cast state, making it difficult to completely release deep residual stress and eliminate grain boundary segregation while maintaining near-net size. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a near-net-shape forming and thermal stress optimization process for complex component metal materials. This process solves the problems of asynchronous cooling of different cross sections of components due to the fixed heat transfer rate of conventional cooling media, uneven volume shrinkage leading to thermal stress concentration and deformation cracking, and the inability of a single heat treatment to completely release residual stress.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A near-net-shape forming and thermal stress optimization process for complex component metal materials, the process comprising the following steps:

[0008] Antioxidant 703 and benzotriazole were added to propylene glycol and heated to dissolve to prepare a composite additive solution;

[0009] An adaptive phase change heat transfer fluid was prepared by mixing polyalkylene glycol, the composite additive liquid, and deionized water, and the conformal temperature control channel inside the molding die was designed in reverse based on the thermal stress simulation analysis results of the complex component.

[0010] The molten aluminum alloy is injected into the preheated forming mold and die-casting pressure is applied. At the same time, the adaptive phase change heat transfer fluid is pumped into the conformal temperature control channel to control the cooling rate of the thermal stress concentration area, thereby completing near-net-shape forming and obtaining a preliminary complex component.

[0011] The initially formed complex component is subjected to multi-stage heating and heat preservation heat treatment, and then slowly cooled to room temperature in the furnace.

[0012] By employing the technical solution of this invention, dynamic thermal field control is implemented using an adaptive phase change heat transfer fluid combined with a conformal temperature control channel, and assisted by multi-stage heating and heat preservation heat treatment, the effects of suppressing thermal stress generation and eliminating residual stress from the source are achieved. The specific mechanism and reaction process are as follows:

[0013] In the composite additive solution, the nitrogen atom of benzotriazole uses its lone pair electrons to establish a coordination bond with the metal, forming a complex protective film to resist flow channel corrosion. Antioxidant 703 releases active hydrogen atoms to interrupt the oxidation chain reaction of the system and maintain the high-temperature chemical stability of polyalkylene glycol.

[0014] At low temperatures, polyalkylene glycol molecules maintain a uniform dissolved state by forming hydrogen bonds with water through ether bonds. When flowing through the high-temperature mold area, the hydrogen bonds break, triggering a conformational change in the polymer and causing it to desolvate from the aqueous phase and precipitate out, forming an insulating layer on the inner wall of the flow channel. As the local temperature rises and falls, the thickness of the insulating layer dynamically increases or decreases, adaptively adjusting the contact thermal resistance between the fluid and the mold interface.

[0015] Combining the latent heat absorption of phase change vaporization during the boiling stage of deionized water, the fluid slows down the heat exchange by thickening the insulation layer in the area where heat accumulates highly. In the thin-walled area where the heat is relatively low, no polymer is precipitated, thus maintaining efficient heat transfer. The physical adaptive damping mechanism reduces the overall temperature gradient of the mold, causing the cooling rate of different cross-sectional thickness areas to tend to be consistent, thus offsetting the tensile stress accumulated by the solidification shrinkage time difference.

[0016] Subsequent multi-stage heating and holding alternating operations stimulate fault slip and climb annihilation phenomena in the matrix, and residual internal stress gradually dissipates with microscopic plastic deformation. In conjunction with the short-range diffusion behavior of alloying elements, grain boundary segregation is eliminated, and the grain structure is homogenized and the physical size is fixed.

[0017] Preferably, the step of adding antioxidant 703 and benzotriazole to propylene glycol and heating to dissolve them to prepare the composite additive solution includes:

[0018] Add 0.05 to 0.4 parts by weight of antioxidant 703 and 0.05 to 0.1 parts by weight of benzotriazole to 1.0 to 3.0 parts by weight of propylene glycol, and heat the propylene glycol to 50°C while stirring continuously until completely dissolved.

[0019] By employing the technical solution of this invention, propylene glycol, as a co-solvent, reduces the surface tension of the mixture of antioxidant 703 and benzotriazole, promotes their dissolution and diffusion, limits the specific component ratio so that the concentration of benzotriazole is within a reasonable range, and establishes a monolayer complex film on the surface of the metal flow channel. At the same time, it prevents excessive precipitation of antioxidant 703 from reducing the specific heat capacity of the heat transfer fluid or clogging the flow channel, thus maintaining the stability of the thermophysical properties of the system.

[0020] Preferably, the step of preparing the adaptive phase change heat transfer fluid by mixing polyalkylene glycol, the composite additive liquid, and deionized water includes:

[0021] Add 5.0 to 15.0 parts by weight of polyalkylene glycol with a number average molecular weight of 2000 to 5000 and a molar ratio of ethylene oxide to propylene oxide of 1:1 to 1:3 to a mixing tank. Then start mechanical stirring and set the speed to 200 to 400 r / min. Then pour in the composite additive liquid and mix evenly to obtain an organic concentrate.

[0022] By adopting the technical solution of this invention, the molecular weight of polyalkylene glycol and the monomer molar ratio parameters jointly affect the cloud point temperature of the fluid and the adhesion strength of the precipitated film. The molecular weight is in the range of 2000 to 5000, which helps the fluid maintain a suitable kinematic viscosity and reduces pumping resistance. The hydrophobic groups provided by propylene oxide and the hydrophilic groups provided by ethylene oxide, combined with a ratio range of 1:1 to 1:3, make the polymer desolvation and precipitation temperature match the cooling temperature control range of the aluminum alloy die-casting mold, which promotes the rapid formation of the insulation layer in the high-temperature environment and the resolvation during the cooling stage.

[0023] Preferably, the step of preparing the adaptive phase change heat transfer fluid by mixing polyalkylene glycol, the composite additive liquid, and deionized water includes:

[0024] While maintaining the stirring speed, add 81.5 to 93.9 parts by weight of deionized water at a temperature of 20 to 30°C dropwise to the mixed organic concentrate. After the addition is complete, maintain the temperature of 20 to 30°C and stir continuously for 30 to 60 minutes until a homogeneous and stable state is achieved.

[0025] By adopting the technical solution of this invention, the proportion of deionized water is limited to provide a basic specific heat capacity reserve and latent heat of phase change vaporization for the entire fluid system. The dropwise addition operation is performed within a specific temperature range and the stirring time is controlled, which promotes the establishment of a uniform hydrogen bond network between polyalkylene glycol and deionized water molecules, prevents the premature aggregation and gelation of polymers caused by excessively high local concentrations, and maintains the thermodynamic phase stability of the heat transfer fluid in a normal temperature environment.

[0026] Preferably, the step of reverse-engineering the conformal temperature-controlled flow channel inside the molding die based on the thermal stress simulation analysis results of complex components includes:

[0027] Within the software, thermal stress simulation analysis is performed to extract thin-walled feature areas, variable cross-section junction areas, asymmetric protrusion areas, or acute-angle joint areas of complex components as thermal stress concentration areas.

[0028] By adopting the technical solution of this invention, the four types of geometric abrupt change regions correspond to the key positions where the physical constraints of the metal solidification and shrinkage stage are prominent and the temperature gradient is induced. The specific regions are extracted as thermal stress concentration areas and the conformal temperature control channels are arranged in a targeted manner. This allows the cooling regulation effect of the adaptive phase change heat transfer fluid to be guided to the high-risk nodes, thereby improving the overall temperature field distribution uniformity of the mold.

[0029] Preferably, the step of injecting the molten aluminum alloy into the preheated forming mold and applying die-casting pressure includes:

[0030] The 7075 aluminum alloy ingot is completely melted at a temperature of 720 to 750°C to obtain molten aluminum alloy. At the same time, the forming mold is preheated to 200 to 250°C. Then, the molten aluminum alloy is injected into the cavity of the forming mold and a die-casting pressure of 50 to 70 MPa is applied.

[0031] By adopting the technical solution of this invention, the aluminum alloy is liquefied and good filling fluidity is obtained in the temperature range of 720 to 750°C, preventing the generation of cold shut defects. The molding die is preheated to 200 to 250°C to reduce the initial temperature difference between the aluminum liquid and the mold wall, reduce the sensitivity of surface chilling effect to cracks, and the pressure of 50 to 70 MPa overcomes the filling resistance, improves the dense state of the metal liquid during the solidification stage, and reduces internal shrinkage cavities.

[0032] Preferably, the step of simultaneously pumping the adaptive phase change heat transfer fluid into the conformal temperature-controlled flow channel to control the cooling rate of the thermal stress concentration zone includes:

[0033] By utilizing the phase change heat transfer characteristics of the adaptive phase change heat transfer fluid, the cooling rate of the thermal stress concentration zone is kept constant at 15 to 35 °C / s, thereby offsetting the internal thermal stress generated by the solidification shrinkage of the material.

[0034] By adopting the technical solution of this invention, the cooling rate is controlled to be constant within the range of 15 to 35℃ / s, suppressing the grain boundary segregation induced by non-equilibrium solidification, mitigating the local enrichment of alloying elements, and promoting the synchronous state of volume shrinkage of the thick and thin sections of the component within the rate range, thereby offsetting the tensile stress accumulated during the solid phase transformation and shrinkage superposition process from a physical scale.

[0035] Preferably, the step of completing near-net-shape forming to obtain a preliminary complex component includes:

[0036] The pressure is held for 10 to 20 seconds to complete the near-net-shape forming, and finally the complex component is demolded and removed.

[0037] By adopting the technical solution of this invention, the pressure holding operation is maintained for 10 to 20 seconds in the near-net-shape stage, which causes the injection punch to continuously apply static pressure to the uncured molten metal, and to perform forced feeding to the volume shrinkage area. The static pressure feeding operation promotes the transformation of the liquid phase in the core to the solid phase, constructs the crystal skeleton structure, and maintains the near-net-shape dimensional accuracy.

[0038] Preferably, the step of performing multi-stage heating and heat preservation heat treatment on the initially formed complex component includes:

[0039] The first stage is set to heat to 120 to 140°C at a heating rate of 3 to 5°C / min and hold for 2 to 3 hours.

[0040] By adopting the technical solution of this invention, the first stage of heat treatment promotes the decomposition of supersaturated solid solution in the aluminum alloy matrix, precipitates micro-solute atom aggregation areas, controls the heating rate to be in the range of 3 to 5℃ / min to prevent secondary thermal stress from being generated inside and outside the material, and provides short-range diffusion of solute atoms with the time span, providing particle distribution for strengthening phase nucleation, and initially relaxing the macroscopic internal stress accumulated in the die casting process.

[0041] Preferably, the step of performing multi-stage heating and heat preservation heat treatment on the initially formed complex component includes:

[0042] The second stage is set to heat to 160 to 170°C at a heating rate of 2 to 4°C / min and hold for 4 to 5 hours.

[0043] By adopting the technical solution of this invention, the second-stage heat treatment promotes the transformation of the pre-aggregate region into strengthening phase particles. The matrix lattice distortion energy is released by the gradual heating combined with the heat preservation mechanism, the deep residual stress is eliminated, and the slow furnace cooling operation is implemented to resist the thermal shock phenomenon of room temperature quenching, solidify the grain structure, and maintain the dimensional stability and mechanical strength of the component.

[0044] This invention provides a near-net-shape forming and thermal stress optimization process for complex metal components. It offers the following advantages:

[0045] 1. This invention utilizes an adaptive phase change heat transfer fluid combined with a conformal temperature control channel to establish a dynamic thermal field control mechanism. Polyalkylene glycol decomposes and precipitates upon heating and adheres to the inner wall of the channel to form a polymer-rich insulating layer. When the temperature decreases, it redissolves. Combined with the absorption of latent heat by the phase change vaporization of deionized water, the contact thermal resistance between the fluid and the mold interface is adaptively adjusted. Physical thermal resistance adjustment is implemented for different cross-sectional thickness areas of complex components, reducing the overall temperature gradient of the mold and maintaining a consistent cooling rate in each area. This counteracts the volume shrinkage differences caused by solidification time differences and suppresses warping deformation and microcracks during the molding process.

[0046] 2. This invention enhances corrosion resistance and thermal cycling stability by introducing a composite additive with a specific ratio into the heat transfer medium. The nitrogen atoms in benzotriazole establish coordination bonds with metal atoms through lone pair electrons, forming a multi-molecular complex protective film on the flow channel surface to resist high-temperature water flow erosion and corrosion. Antioxidant 703 provides active hydrogen atoms to participate in the reaction, interrupting the oxidation chain reaction path and preventing polyalkylene glycol from degrading or excessively agglomerating and gelling under high-temperature alternating environment, thus maintaining the long-term stability of the system's thermophysical properties.

[0047] 3. This invention eliminates residual stress in components and promotes microstructure homogenization by relying on multi-stage heating and heat treatment combined with slow furnace cooling. It uses a progressively set heating rate and staged heat treatment span to induce slip and climb annihilation behavior of faults in the metal matrix, avoiding secondary thermal stress induced by temperature difference between the inside and outside of the component. The accompanying micro-plastic deformation process promotes the decomposition of supersaturated solid solution, and the short-range diffusion of alloying elements eliminates grain boundary segregation caused by non-equilibrium solidification, thus completing the physical dimension shaping and mechanical strength improvement of the formed component. Attached Figure Description

[0048] Figure 1 This is a schematic diagram of the heat flux variation curve of differential scanning calorimetry according to the present invention;

[0049] Figure 2 This is a schematic diagram of the local heat transfer coefficient fluctuation curve over time according to the present invention.

[0050] Figure 3 This is a schematic diagram of the thermogravimetric retention rate of the present invention as a function of time.

[0051] Figure 4 This is a schematic diagram of the infrared absorbance variation curve of the present invention;

[0052] Figure 5 The diffraction peak position shift of the present invention varies with sin 2 Schematic diagram of the ψ variation curve;

[0053] Figure 6 This is a schematic diagram of the spatial distribution fluctuation curve of the dimensional deviation along the measurement path according to the present invention;

[0054] Figure 7 This is a schematic diagram of the engineering stress and engineering strain response curves of the present invention. Detailed Implementation

[0055] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0056] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0057] Polyalkylene glycol, CAS No. 31694-55-0, is a water-soluble polymer formed by random copolymerization of ethylene oxide and propylene oxide, wherein the number average molecular weight ranges from 2000 to 5000 and the molar ratio of ethylene oxide to propylene oxide is 1:1 to 1:3.

[0058] Propylene glycol, CAS number 57-55-6, specifically 1,2-propanediol, with a purity of not less than 99.5 wt%.

[0059] Antioxidant 703, CAS number 88-27-7, is 2,6-di-tert-butyl-4-(dimethylaminomethyl)phenol, with a purity of not less than 98.0 wt%.

[0060] Benzotriazole, CAS number 95-14-7, purity not less than 99.0 wt%.

[0061] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.

[0062] Example 1:

[0063] This embodiment provides a near-net-shape forming and thermal stress optimization process for complex component metal materials, including the following steps:

[0064] 0.05 parts by weight of antioxidant 703 and 0.05 parts by weight of benzotriazole were added to 1.0 parts by weight of propylene glycol, and the propylene glycol was heated to 50°C and stirred continuously until completely dissolved to prepare a composite additive solution.

[0065] Add 5.0 parts by weight of polyalkylene glycol with a number average molecular weight of 2000 and a molar ratio of ethylene oxide to propylene oxide of 1:1 to the mixing tank. Then start the mechanical stirring and set the speed to 200 r / min. Pour in the prepared composite additive liquid and stir to mix evenly to obtain an organic concentrate. Maintain the stirring speed of 200 r / min and add 93.9 parts by weight of deionized water at 20°C to the organic concentrate. After the addition is completed, maintain the temperature at 20°C and stir continuously for 30 minutes until a homogeneous and stable state is reached, thereby obtaining an adaptive phase change heat transfer fluid. Then, establish a three-dimensional digital model of the complex component and import it into the finite element analysis software. Then, perform thermal stress simulation analysis in the software to extract the thin-walled feature area of ​​the complex component as the thermal stress concentration area. Finally, based on the thermal stress simulation analysis results, reverse design the conformal temperature control flow channel inside the molding die.

[0066] 7075 aluminum alloy ingots are placed in a melting furnace and heated to 720°C to be completely melted to obtain molten aluminum alloy. At the same time, the forming mold is preheated to 200°C. Then, the molten aluminum alloy is injected into the cavity of the forming mold and a die-casting pressure of 50 MPa is applied. Simultaneously, a circulating pump is started to pump the adaptive phase change heat transfer fluid into the conformal temperature control channel for zoned dynamic thermal field control. During this process, the phase change heat transfer fluid's phase change heat absorption characteristics are used to control the cooling rate of the thermal stress concentration area to be kept constant at 35°C / s, thereby offsetting the internal thermal stress generated by the solidification shrinkage of the material. Then, the pressure is held for 10 seconds to complete near-net-shape forming. Finally, the initial-formed complex component is demolded and removed.

[0067] The initially formed complex component is placed in a heat treatment furnace for multi-stage heating and holding heat treatment. First, the first stage is set to heat to 120°C at a heating rate of 3°C / min and hold for 2 hours. Then, the second stage is set to heat to 160°C at a heating rate of 2°C / min and hold for 4 hours. After that, the power to the heat treatment furnace is turned off, and the initially formed complex component is allowed to cool slowly to room temperature with the heat treatment furnace. This allows for the full release of residual stress and the homogenization of the microstructure without damaging the near-net size.

[0068] Example 2:

[0069] This embodiment provides a near-net-shape forming and thermal stress optimization process for complex component metal materials, including the following steps:

[0070] 0.2 parts by weight of antioxidant 703 and 0.1 parts by weight of benzotriazole were added to 2.0 parts by weight of propylene glycol, and the propylene glycol was heated to 50°C and stirred continuously until completely dissolved to prepare a composite additive solution.

[0071] 10.0 parts by weight of polyalkylene glycol with a number average molecular weight of 3500 and a molar ratio of ethylene oxide to propylene oxide of 1:2 were added to the mixing tank. Then, mechanical stirring was started and the speed was set to 300 r / min. The prepared composite additive solution was then poured in and stirred to obtain an organic concentrate. While maintaining the stirring speed of 300 r / min, 87.7 parts by weight of deionized water at 25°C was added dropwise to the organic concentrate. After the addition was completed, the temperature was maintained at 25°C and stirred continuously for 45 minutes until a homogeneous and stable state was achieved, thus obtaining an adaptive phase change heat transfer fluid. Then, a three-dimensional digital model of the complex component was established and imported into the finite element analysis software. The thermal stress simulation analysis was then performed in the software to extract the variable cross-section interface area of ​​the complex component as the thermal stress concentration area. Finally, based on the thermal stress simulation analysis results, the conformal temperature control flow channel inside the molding die was designed in reverse.

[0072] 7075 aluminum alloy ingots are placed in a melting furnace and heated to 735°C to be completely melted to obtain molten aluminum alloy. At the same time, the forming mold is preheated to 225°C. Then, the molten aluminum alloy is injected into the cavity of the forming mold and a die-casting pressure of 60 MPa is applied. Simultaneously, a circulating pump is started to pump the adaptive phase change heat transfer fluid into the conformal temperature control channel for zoned dynamic thermal field control. During this process, the phase change heat transfer fluid's phase change endothermic characteristics are used to control the cooling rate of the thermal stress concentration area to be kept constant at 25°C / s, thereby offsetting the internal thermal stress generated by the solidification shrinkage of the material. Then, the pressure is held for 15 seconds to complete near-net-shape forming. Finally, the initial complex component is demolded and removed.

[0073] The initially formed complex component is placed in a heat treatment furnace for multi-stage heating and holding heat treatment. First, the first stage is set to heat to 130°C at a heating rate of 4°C / min and hold for 2.5 hours. Then, the second stage is set to heat to 165°C at a heating rate of 3°C / min and hold for 4.5 hours. After that, the power to the heat treatment furnace is turned off, and the initially formed complex component is allowed to cool slowly to room temperature with the heat treatment furnace. This allows for the full release of residual stress and the homogenization of the microstructure without damaging the near-net-shape.

[0074] Example 3:

[0075] This embodiment provides a near-net-shape forming and thermal stress optimization process for complex component metal materials, including the following steps:

[0076] 0.4 parts by weight of antioxidant 703 and 0.1 parts by weight of benzotriazole were added to 3.0 parts by weight of propylene glycol, and the propylene glycol was heated to 50°C and stirred continuously until completely dissolved to prepare a composite additive solution.

[0077] 15.0 parts by weight of polyalkylene glycol with a number-average molecular weight of 5000 and a molar ratio of ethylene oxide to propylene oxide of 1:3 were added to the mixing tank. Then, mechanical stirring was started and the speed was set to 400 r / min. The prepared composite additive solution was then poured in and stirred to obtain an organic concentrate. While maintaining the stirring speed of 400 r / min, 81.5 parts by weight of deionized water at 30°C were added dropwise to the organic concentrate. After the addition was completed, the temperature was maintained at 30°C and the mixture was stirred continuously for 60 minutes until a homogeneous and stable state was achieved, thus obtaining an adaptive phase change heat transfer fluid. A three-dimensional digital model of the complex component was then established and imported into the finite element analysis software. The asymmetric protrusion area of ​​the complex component was extracted as the thermal stress concentration area by thermal stress simulation analysis in the software. Finally, the conformal temperature control flow channel inside the molding die was designed in reverse based on the thermal stress simulation analysis results.

[0078] 7075 aluminum alloy ingots are placed in a melting furnace and heated to 750°C to be completely melted to obtain molten aluminum alloy. At the same time, the forming mold is preheated to 250°C. Then, the molten aluminum alloy is injected into the cavity of the forming mold and a die-casting pressure of 70 MPa is applied. Simultaneously, a circulating pump is started to pump the adaptive phase change heat transfer fluid into the conformal temperature control channel for zoned dynamic thermal field control. During this process, the phase change heat transfer fluid's phase change heat absorption characteristics are used to control the cooling rate of the thermal stress concentration area to be kept constant at 15°C / s, thereby offsetting the internal thermal stress generated by the solidification shrinkage of the material. Then, the pressure is held for 20 seconds to complete near-net-shape forming. Finally, the initial-formed complex component is demolded and removed.

[0079] The initially formed complex component is placed in a heat treatment furnace for multi-stage heating and holding heat treatment. First, the first stage is set to heat to 140°C at a heating rate of 5°C / min and hold for 3 hours. Then, the second stage is set to heat to 170°C at a heating rate of 4°C / min and hold for 5 hours. After that, the power to the heat treatment furnace is turned off, and the initially formed complex component is allowed to cool slowly to room temperature with the heat treatment furnace. This allows for the full release of residual stress and the homogenization of the microstructure without damaging the near-net size.

[0080] Example 4:

[0081] This embodiment provides a near-net-shape forming and thermal stress optimization process for complex component metal materials, including the following steps:

[0082] 0.3 parts by weight of antioxidant 703 and 0.1 parts by weight of benzotriazole were added to 2.5 parts by weight of propylene glycol, and the propylene glycol was heated to 50°C and stirred continuously until completely dissolved to prepare a composite additive solution.

[0083] Then, 12.0 parts by weight of polyalkylene glycol with a number-average molecular weight of 4000 and a molar ratio of ethylene oxide to propylene oxide of 1:2 were added to the mixing tank. Mechanical stirring was then started and the speed was set to 350 r / min. The prepared composite additive solution was then poured in and stirred to obtain an organic concentrate. While maintaining the stirring speed of 350 r / min, 85.1 parts by weight of deionized water at a temperature of 28°C were added dropwise to the organic concentrate. After the addition was completed, the temperature was maintained at 28°C and the mixture was stirred continuously for 50 minutes until a homogeneous and stable state was achieved, thus obtaining an adaptive phase change heat transfer fluid. Next, a three-dimensional digital model of the complex component was established and imported into the finite element analysis software. Then, thermal stress simulation analysis was performed in the software to extract the acute angle joint area of ​​the complex component as the thermal stress concentration area. Finally, based on the thermal stress simulation analysis results, the conformal temperature control flow channel inside the molding die was designed in reverse.

[0084] 7075 aluminum alloy ingots are placed in a melting furnace and heated to 740℃ to be completely melted to obtain molten aluminum alloy. At the same time, the forming mold is preheated to 235℃. Then, the molten aluminum alloy is injected into the cavity of the forming mold and a die-casting pressure of 65 MPa is applied. Simultaneously, a circulating pump is started to pump the adaptive phase change heat transfer fluid into the conformal temperature control channel for zoned dynamic thermal field control. During this process, the phase change heat transfer fluid's phase change heat absorption characteristics are used to control the cooling rate of the thermal stress concentration area to be kept constant at 20℃ / s, thereby offsetting the internal thermal stress generated by the solidification shrinkage of the material. Then, the pressure is held for 18 seconds to complete near-net-shape forming. Finally, the initial-formed complex component is demolded and removed.

[0085] The initially formed complex component is placed in a heat treatment furnace for multi-stage heating and holding heat treatment. First, the first stage is set to heat to 135℃ at a heating rate of 4.5℃ / min and hold for 2.8 hours. Then, the second stage is set to heat to 168℃ at a heating rate of 3.5℃ / min and hold for 4.8 hours. After that, the power to the heat treatment furnace is turned off, and the initially formed complex component is allowed to cool slowly to room temperature with the heat treatment furnace. This allows for the full release of residual stress and the homogenization of the microstructure without damaging the near-net size.

[0086] Comparative Example 1:

[0087] Compared with Example 2, the difference is that propylene glycol is not added to the formula and the original weight of propylene glycol is completely replaced by deionized water, while the rest are the same.

[0088] Comparative Example 2:

[0089] Compared with Example 2, the difference is that antioxidant 703 is not added to the formula and the weight portion originally occupied by antioxidant 703 is completely replaced by deionized water, while the rest are the same.

[0090] Comparative Example 3:

[0091] Compared with Example 2, the difference is that the multi-stage heating and heat preservation heat treatment is replaced with a single-stage annealing process and the first-stage low-temperature heat preservation platform is completely eliminated, and the temperature is directly raised to 165°C for constant heat preservation. All other aspects are the same.

[0092] Test Example 1:

[0093] 10 mg of each of the adaptive phase change heat transfer fluid samples prepared in Example 1, Example 2 and Comparative Example 1 were measured, placed in a standard aluminum crucible and sealed by pressing. An empty aluminum crucible was used as a reference. The test was conducted under a nitrogen atmosphere. The test temperature range was set from 20 °C to 120 °C and the heating rate was set to 5 °C / min. The differential scanning calorimetry heat flow change curves during the test were recorded. The starting temperature and ending temperature of the phase change endothermic peak were calculated based on the differential scanning calorimetry heat flow change curves. The difference between the starting temperature and the ending temperature was taken as the phase change temperature window width.

[0094] The adaptive phase change heat transfer fluid samples prepared in Examples 1, 2, and Comparative Example 1 were subjected to temperature-induced viscosity scanning tests using a rotational rheometer. A coaxial cylindrical test fixture was used, and the test shear rate was set to a constant 50 s⁻¹. -1 The test program was set to heat from 25℃ to 95℃ at a rate of 2℃ / min. Data points of apparent viscosity of each sample were collected to continuously change with temperature to generate an apparent viscosity-temperature curve. The data were then differentiated to extract the maximum slope of the viscosity abrupt change interval.

[0095] A pipeline thermal-hydraulic test bench was constructed, comprising a constant-temperature heating block, a stainless steel circular tube experimental section with an inner diameter of 8 mm, and a high-frequency data acquisition system. The surface temperature of the constant-temperature heating block was kept constant at 200℃. The adaptive phase change heat transfer fluids prepared in Examples 1, 2, and Comparative Example 1 were pumped into the pipeline thermal-hydraulic test bench at a constant inlet flow rate of 0.5 m / s. After the system reached thermal equilibrium through circulation, the changes in the local heat transfer coefficient of the experimental section were continuously recorded over 600 seconds to generate a local heat transfer coefficient fluctuation curve over time. The relative standard deviation of the local heat transfer coefficient in the local heat transfer coefficient fluctuation curve over time was extracted as a quantitative evaluation index of the fluid heat transfer stability.

[0096] The test results are shown in Table 1.

[0097] Table 1. Summary of test data for thermodynamic, rheological, and heat transfer parameters of Examples 1, 2, and Comparative Example 1:

[0098] Sample Name Phase change endothermic peak onset temperature (°C) Termination temperature of the phase change endothermic peak (°C) Phase transition temperature window width (°C) Maximum slope of viscosity change (mPa·s / ℃) Relative standard deviation of local heat transfer coefficient (%) Example 1 46.3 79.8 33.5 12.7 3.2 Example 2 49.1 84.7 35.6 14.2 2.6 Comparative Example 1 61.4 68.2 6.8 114.9 36.5

[0099] According to Table 1 and appendix Figure 1 and attached Figure 2The data shows that the phase change temperature window widths of Example 1 and Example 2 are 33.5℃ and 35.6℃, respectively, while the phase change temperature window width of Comparative Example 1 is 6.8℃. The hydroxyl groups in the propylene glycol molecule construct a competitive hydrogen bond effect inside the adaptive phase change heat transfer fluid, which interferes with the dehydration and aggregation kinetics of polymer chain segments, transforming the concentrated phase separation process into a phase change process that unfolds over a wider temperature range.

[0100] The maximum slope of viscosity abrupt change in Comparative Example 1 was 114.9 mPa·s / ℃, reflecting the increased flow resistance caused by the large amount of polyalkylene glycol segments precipitated near the critical temperature. The maximum slopes of viscosity abrupt change in Examples 1 and 2 were 12.7 mPa·s / ℃ and 14.2 mPa·s / ℃, respectively. The smooth viscosity transition state suppressed the abrupt changes in the macroscopic physical properties of the adaptive phase change heat transfer fluid.

[0101] The relative standard deviation of the local heat transfer coefficient in Comparative Example 1 was 36.5%. The narrow phase change window caused disordered local deposition of polymer on the heating tube wall, resulting in overheating of the bottom layer of the heated boundary and inducing boiling cavitation. The relative standard deviations of the local heat transfer coefficients in Examples 1 and 2 were 3.2% and 2.6%, respectively. The wider phase change temperature window enabled the adaptive phase change heat transfer fluid to form a polymer isolation film in a dynamic dissolution-deposition equilibrium state when in contact with the high-temperature boundary, maintaining stable heat transfer performance and reducing the risk of cavitation and blockage in the molding equipment pipeline system.

[0102] Test Example 2:

[0103] 15 mg of each of the adaptive phase change heat transfer fluid samples prepared in Example 2, Example 3 and Comparative Example 2 were measured and placed in the alumina crucible of the thermogravimetric analyzer. Under the test atmosphere with an air flow rate of 50 mL / min, the temperature of the test chamber was heated to 150 °C at a heating rate of 10 °C / min. The temperature was kept constant at 150 °C for 10 hours. The data of the continuous change of sample mass over time during the test were recorded to generate a data set of the thermogravimetric retention rate over time. Based on the generated data set, the thermogravimetric retention rate value and the maximum rate of thermogravimetric loss after 10 hours of constant temperature were extracted.

[0104] The adaptive phase change heat transfer fluid samples prepared in Examples 2, 3, and Comparative Example 2 were measured and placed in glass petri dishes. The petri dishes containing the adaptive phase change heat transfer fluid samples were then placed in a forced-air drying oven set at 150°C for accelerated oxidation treatment for 10 hours. The adaptive phase change heat transfer fluid samples before and after accelerated oxidation treatment were then coated onto the surface of a potassium bromide wafer. Fourier transform infrared spectroscopy was used to analyze the samples at 4000 cm⁻¹. -1 Up to 400cm -1The scanning test was conducted within the wavenumber range, and the extracted wavenumber was 1720 cm⁻¹. -1 Nearby test data were used to record the absorbance values ​​of the carbonyl characteristic peak before and after accelerated oxidation treatment.

[0105] The test results are shown in Table 2.

[0106] Table 2. Summary of high-temperature oxidation resistance and anti-coking performance test data of Examples 2, 3 and Comparative Example 2:

[0107] Sample Name Thermogravimetric retention rate (%) after 10 hours of constant temperature Maximum rate of thermogravimetric loss (% / h) Absorbance (AU) of the carbonyl characteristic peak before heat treatment Absorbance (AU) of the carbonyl characteristic peak after heat treatment Example 2 98.6 0.14 0.021 0.038 Example 3 97.4 0.19 0.016 0.042 Comparative Example 2 64.1 7.92 0.018 0.814

[0108] According to Table 2 and appendix Figure 3 and attached Figure 4 The data show that the thermogravimetric retention rate after 10 hours of constant temperature in Example 2 was 98.6%, while that in Comparative Example 2 was 64.1%. The difference between the absorbance of the carbonyl characteristic peak before and after heat treatment in Example 2 was less than 0.03, while the difference between the absorbance of the carbonyl characteristic peak before and after heat treatment in Comparative Example 2 was 0.796.

[0109] Antioxidant 703 establishes a free radical capture pathway within the adaptive phase change heat transfer fluid. Under high-temperature heating conditions, the carbon-hydrogen bonds of the polyalkylene glycol molecular chain break, generating alkyl free radicals and peroxy free radicals. The phenolic hydroxyl group in the structure of antioxidant 703 provides hydrogen atoms, which combine with the peroxy free radicals to generate hydroperoxides and phenolic oxygen free radicals. The tert-butyl group in the structure of antioxidant 703 provides steric hindrance, restricting the coupling reaction between phenolic oxygen free radicals and other molecules in the adaptive phase change heat transfer fluid, thus interrupting the catalytic oxidation process of the polyalkylene glycol molecular chain.

[0110] In Comparative Example 2, the polyalkylene glycol molecular chain breaks down and generates volatile products containing carbonyl groups, resulting in a decrease in the thermogravimetric retention rate of Comparative Example 2 and an increase in the absorbance of the carbonyl characteristic peak in the infrared spectrum. The adaptive phase change heat transfer fluids of Examples 2 and 3, combined with the steric hindrance effect and free radical capture pathway, slow down the degradation rate of the polyalkylene glycol molecular skeleton and prevent the polyalkylene glycol molecules from carbonizing and coking at extreme mold wall temperatures.

[0111] Test Example 3:

[0112] The components prepared in Examples 2, 4, and 3 were analyzed using an X-ray diffractometer combined with sin 2 Residual stress was tested using the ψ method. During the test, the X-ray incident angle was gradually changed, and the positions of diffraction peaks at multiple different ψ angles were recorded. The diffraction peak position shift was then analyzed as a function of sin... 2The linear relationship of ψ was used to calculate the residual stress values ​​of the component before and after heat treatment, and the residual stress elimination rate was calculated based on the residual stress values ​​before and after heat treatment.

[0113] A coordinate measuring machine was used to perform three-dimensional scanning tests on the feature areas of the heat-treated components prepared in Examples 2, 4 and Comparative Example 3. The three-dimensional point cloud data generated by the scanning was extracted, and the coordinates of the three-dimensional point cloud data were aligned and the deviation was compared with the standard computer-aided design model of the component. The contour data on the component measurement path was extracted, the macroscopic dimensional deviation values ​​of each spatial acquisition point on the measurement path were calculated, the spatial distribution fluctuation curve of the dimensional deviation along the measurement path was generated, the macroscopic dimensional deviation values ​​of all spatial acquisition points were statistically analyzed, and the mean and standard deviation of the dimensional deviation were calculated.

[0114] The test results are shown in Table 3.

[0115] Table 3. Summary of test data on residual stress and macroscopic dimensional deviations for Examples 2, 4 and Comparative Example 3:

[0116] Sample Name Residual stress (MPa) before heat treatment Residual stress (MPa) after heat treatment Residual stress relief rate (%) Mean dimensional deviation (mm) Standard deviation of dimensional deviation (mm) Example 2 315.4 42.6 86.49 0.012 0.004 Example 4 308.7 38.2 87.63 0.015 0.005 Comparative Example 3 321.2 84.9 73.57 0.187 0.062

[0117] According to Table 3 and appendix Figure 5 and attached Figure 6 The data shows that the residual stress relief rate of Example 2 was 86.49%, and the residual stress relief rate of Comparative Example 3 was 73.57%. The mean dimensional deviation of Example 2 was 0.012 mm, and the standard deviation of dimensional deviation was 0.004 mm. The mean dimensional deviation of Comparative Example 3 was 0.187 mm, and the standard deviation of dimensional deviation was 0.062 mm.

[0118] Multi-stage heating and heat treatment distributes the stress release process inside the component to different temperature ranges through a gradient heating process. Under the set temperature plateau, the internal lattice of the component material generates a small amount of slip motion. The small amount of slip motion converts the elastic energy accumulated by lattice distortion into heat energy and releases it. The small amount of slip motion is confined to the local grain range, suppressing the tendency of plastic yielding phenomenon at the overall level of the component.

[0119] Comparative Example 3 uses a single-stage annealing method. The temperature jump causes instantaneous plastic yielding inside the component material, resulting in uneven macroscopic deformation in the stress concentration area. The macroscopic deformation test results show that the dimensional deviation curve of Comparative Example 3 has large fluctuation peaks. Examples 2 and 4 use multi-stage heating and heat preservation heat treatment to control sub-yield state micro-creep and macroscopic deformation, release internal residual stress while maintaining a low average dimensional deviation, and prevent macroscopic warping deformation of the component during the heat treatment process.

[0120] Test Example 4:

[0121] The components prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were taken respectively, and the prepared components were processed into metal tensile specimens. Axial tensile tests were performed on the metal tensile specimens using a universal testing machine. The tensile speed was set to 2 mm / min. The load and displacement values ​​during the test were recorded. The engineering stress and engineering strain were calculated based on the load and displacement values, and the engineering stress and engineering strain response curves were generated. The coordinates of the yield strength point and the fracture point in the engineering stress and engineering strain response curves were extracted, and the yield strength value and the fracture elongation value were calculated.

[0122] In the die-casting process of components in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3, a multi-channel thermocouple monitoring system integrated inside the mold cavity was used to collect mold wall temperature fluctuation data, record transient cooling rate data in independent die-casting cycles, summarize transient cooling rate collection points in 200 consecutive die-casting cycles, statistically analyze the distribution characteristics of transient cooling rate around the set value of 25℃ / s, and calculate the average cooling rate value and the standard deviation of cooling rate in the die-casting cycle.

[0123] The test results are shown in Table 4.

[0124] Table 4 Summary of test data on comprehensive mechanical properties and molding cooling rate of Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3:

[0125] Sample Name Yield strength (MPa) Elongation at break (%) Average cooling rate during the die-casting cycle (°C / s) Cooling rate deviation from standard deviation (°C / s) Example 2 345.6 12.4 24.8 0.42 Comparative Example 1 287.3 6.1 16.5 4.87 Comparative Example 2 302.8 8.4 19.2 3.51 Comparative Example 3 264.5 5.2 24.6 0.45

[0126] According to Table 4 and appendix Figure 7 The data shows that the fracture elongation of Example 2 was 12.4%, the average cooling rate during the die casting cycle was 24.8℃ / s, the fracture elongation of Comparative Example 1 was 6.1%, and the average cooling rate during the die casting cycle of Comparative Example 2 was 19.2℃ / s.

[0127] Polyalkylene glycol segments precipitate and agglomerate in large quantities near the critical temperature, blocking the conformal temperature control channel inside the mold. The sudden drop in fluid circulation flow rate causes the transient cooling rate of Comparative Example 1 to deviate from the set value. The imbalance of the cooling gradient causes local coarse grain defects in the metal matrix, reducing the fracture elongation of the metal tensile specimen of Comparative Example 1.

[0128] The lack of free radical capture pathways in the fluid leads to oxidative degradation and carbonization coking reactions. The coking products form a thermally insulating layer, causing the average cooling rate to continuously decrease during the die-casting cycle of Comparative Example 2. This reduces heat dissipation efficiency, prolongs the molding cooling time, and weakens the yield strength of the metal tensile specimens in Comparative Example 2.

[0129] Single-stage conventional annealing induces transient thermal stress concentration, which triggers microcrack initiation within the metal matrix. Under tensile load, the microcrack initiation propagates, leading to early brittle fracture of the metal tensile specimen in Comparative Example 3.

[0130] Example 2 maintains a stable cooling rate through an adaptive phase change heat transfer fluid, and controls the micro-slip motion of the crystal lattice through multi-stage heating and heat preservation heat treatment, which limits the generation of micro-cracks. The improved stability of the forming system and the release of micro-residual stress give the metal tensile specimen of Example 2 a balanced mechanical performance of high yield strength and high elongation at break.

[0131] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to the equipment structure, process flow, step sequence, operating parameters, or working medium type in these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the core technical solutions disclosed above and their equivalent substitutions.

Claims

1. A near-net-shape forming and thermal stress optimization process for complex component metal materials, characterized in that, The process includes the following steps: Antioxidant 703 and benzotriazole were added to propylene glycol and heated to dissolve to prepare a composite additive solution; An adaptive phase change heat transfer fluid was prepared by mixing polyalkylene glycol, the composite additive liquid, and deionized water, and the conformal temperature control channel inside the molding die was designed in reverse based on the thermal stress simulation analysis results of the complex component. The molten aluminum alloy is injected into the preheated forming mold and die-casting pressure is applied. At the same time, the adaptive phase change heat transfer fluid is pumped into the conformal temperature control channel to control the cooling rate of the thermal stress concentration area, thereby completing near-net-shape forming and obtaining a preliminary complex component. The initially formed complex component is subjected to multi-stage heating and heat preservation heat treatment, and then slowly cooled to room temperature in the furnace.

2. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 1, characterized in that, The step of adding antioxidant 703 and benzotriazole to propylene glycol and heating to dissolve them to prepare the composite additive solution includes: Add 0.05 to 0.4 parts by weight of antioxidant 703 and 0.05 to 0.1 parts by weight of benzotriazole to 1.0 to 3.0 parts by weight of propylene glycol, and heat the propylene glycol to 50°C while stirring continuously until completely dissolved.

3. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 2, characterized in that, The step of preparing the adaptive phase change heat transfer fluid by mixing polyalkylene glycol, the composite additive liquid, and deionized water includes: Add 5.0 to 15.0 parts by weight of polyalkylene glycol with a number average molecular weight of 2000 to 5000 and a molar ratio of ethylene oxide to propylene oxide of 1:1 to 1:3 to a mixing tank. Then start mechanical stirring and set the speed to 200 to 400 r / min. Then pour in the composite additive liquid and mix evenly to obtain an organic concentrate.

4. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 3, characterized in that, The step of preparing the adaptive phase change heat transfer fluid by mixing polyalkylene glycol, the composite additive liquid, and deionized water includes: While maintaining the stirring speed, add 81.5 to 93.9 parts by weight of deionized water at a temperature of 20 to 30°C dropwise to the mixed organic concentrate. After the addition is complete, maintain the temperature of 20 to 30°C and stir continuously for 30 to 60 minutes until a homogeneous and stable state is achieved.

5. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 1, characterized in that, The steps for reverse-engineering the conformal temperature-controlled flow channel inside the molding die based on the thermal stress simulation analysis results of complex components include: Within the software, thermal stress simulation analysis is performed to extract thin-walled feature areas, variable cross-section junction areas, asymmetric protrusion areas, or acute-angle joint areas of complex components as thermal stress concentration areas.

6. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 1, characterized in that, The step of injecting the molten aluminum alloy into the preheated forming mold and applying die-casting pressure includes: The 7075 aluminum alloy ingot is completely melted at a temperature of 720 to 750°C to obtain molten aluminum alloy. At the same time, the forming mold is preheated to 200 to 250°C. Then, the molten aluminum alloy is injected into the cavity of the forming mold and a die-casting pressure of 50 to 70 MPa is applied.

7. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 1, characterized in that, Simultaneously, the step of pumping the adaptive phase change heat transfer fluid into the conformal temperature-controlled flow channel to control the cooling rate of the thermal stress concentration zone includes: By utilizing the phase change heat transfer characteristics of the adaptive phase change heat transfer fluid, the cooling rate of the thermal stress concentration zone is kept constant at 15 to 35 °C / s, thereby offsetting the internal thermal stress generated by the solidification shrinkage of the material.

8. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 1, characterized in that, The steps for obtaining a preliminary complex component by completing near-net-shape forming include: The pressure is held for 10 to 20 seconds to complete the near-net-shape forming, and finally the complex component is demolded and removed.

9. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 1, characterized in that, The steps of performing multi-stage heating and heat preservation heat treatment on the initially formed complex component include: The first stage is set to heat to 120 to 140°C at a heating rate of 3 to 5°C / min and hold for 2 to 3 hours.

10. The near-net-shape forming and thermal stress optimization process for complex component metal materials according to claim 9, characterized in that, The steps of performing multi-stage heating and heat preservation heat treatment on the initially formed complex component include: The second stage is set to heat to 160 to 170°C at a heating rate of 2 to 4°C / min and hold for 4 to 5 hours.